The influence of shift work on health behavior and self-reported health status of nurses - Kędzierska, Anna; Czerepaniak, Ewelina; Stanisławska, Marzanna; Wieder-Huszla, Sylwia; Wesołowska, Jolanta; Jurczak, Anna (Nursing in the 21st Century, 2019)
THE INFLUENCE OF SHIFT WORK ON HEALTH BEHAVIOR AND SELF-REPORTED HEALTH STATUS OF NURSES Introduction. Working conditions often involve employees’ exposure to factors having adverse effects on their health. Due to its nature, the nursing profession entails numerous risks, associated both with harmful factors and a work system itself. Aim. Aim of this study was to analyze the influence of a shift work system on self-reported health status and health behaviors of nurses. Material and methods. The study included 200 nurses employed in three Szczecin hospitals: the Independent Public Clinical Hospital no. 1, Pomeranian Medical University in Szczecin, Independent Public Clinical Hospital no. 2, Pomeranian Medical University in Szczecin, and Independent Public Voivodeship Integrated Hospital. The research instruments were the Health Behavior Inventory (HBI) developed by Zygfryd Juczyński, and a self-developed questionnaire concerning sociodemographic and medical data. Results. When it comes to 76% of the nurses, they described their health status as good or very good. The majority of the respondents (54%) displayed a low level of health behaviors. The most common work-related complaints were sleep disorders (55%), headaches after return home from work (55%), irritation after return home from work (83%), skin problems (28%), back pains (76%), leg pain/fatigue (84%), and eating disorders (14%). Conclusions. 1. A work system had substantial effect on self-reported health status of the studied group of nurses. 2. The nurses working day shifts displayed a higher level of health behaviors than their counterparts working in a shift system. 3. A day/night shift work pattern correlated with a higher incidence of eating disorders.